Book Review: The Crescent Behind The Thousand Holy Temples: An Ethnographic Study of The Minority Muslims of Pegayaman, North Bali - A.Kristiadji Rahardjo (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2012)
In this interesting book, Erni describes about the efforts or strategies developed by the Muslims of Pegayaman, North Bali to maintain their religious tradition and identities among the Hindu Balinese people. The minority Muslims of Pegayaman have succeeded in maintaining their own cultural identity amidst the majority of population that has the different socio-religious norms. This book focuses on two areas of her field research, that are 1) the Muslims’ defense mechanisms vis-à-vis external challenges to their collective integrity; and 2) the degree to which the Muslims interact with the Hindu population.